Junior entrepreneurship human interactions skills method - Costa-Lobo, Cristina (2019)
Career education emerge in a context of a society where the importance of the ability to anticipate change, adapt to new circumstances, and invent new business practices is explicit. Some social and educational dissatisfaction occurs when the school focuses almost exclusively on the development of the convergent thinking of the students, forgetting the creativity in a divergent and contextual sense. Assuming that creativity is a phenomenon that involves higher levels of consciousness and complexity are addressed didactic options for the pedagogical training of teachers and for the organization of curricular and extracurricular activities of the school, in order to develop participation, problem solving and decision-making, reflection, interaction (through teamwork and networking), teamwork between individuals with different backgrounds, and joint decision-making among actors with complementary. This paper, regarding the entrepreneurial skills, and regarding previous research on entrepreneurship and entrepreneurship education, stresses the role of human interactions skills (HIS) to the success of the entrepreneurial process, both in terms of opportunity discovery/generation and of its exploitation. Entrepreneurship is increasingly regarded as a social process embedded in social structures. One of the most important results of the project-based approaches to learning, strongly recognized in the literature is the development of students' HIS. This view assigns a pivotal role to social capital and to networking in the entrepreneurial process, which can be a complex process requiring the combination of several technological and non-technological competences and resources. These are often external to the entrepreneurial team and distributed across a multiplicity of actors. Networking is therefore a central skill in the entrepreneurial mindset, acting as facilitators in the process of information and resource gathering and in the learning process (learning by interacting). Furthermore, entrepreneurship is frequently a team effort and therefore teamwork skills become central. We emphasize that for entrepreneurship it is indispensable to consider the competence of sustainability, oriented in the objectives of sustainable development for society, as well as the valuation in the local identity of the same with global projection. The Junior Entrepreneurship Human Interactions Skills (JEANS) Method, using a curriculum supported by innovative material and technological resources, enhancing formative evaluation, aims to provide the students the experience to identify and exploit an innovative business idea and develop a project. The steps of training, training carried out and the research plan to assess the competences developed by the JEANS Method are revealed.